Tau mediates the reshaping of the transcriptional landscape toward intermediate Alzheimer’s disease stages - Siano, Giacomo; Varisco, Martina; Terrigno, Marco; Wang, Congwei; Scarlatti, Arianna; Iannone, Vincenzo; Groth, Marco; Galas, Marie-Christine; Hoozemans, Jeroen J. M.; Cellerino, Alessandro; Cattaneo, Antonino; Di Primio, Cristina (Frontiers in Cell and Developmental Biology, 2025)
IntroductionRecent research revealed that Tau plays critical roles in various neuronal functions. We previously demonstrated that destabilization and nuclear delocalization of Tau alter the expression of glutamatergic genes, mediating early neuronal damage.MethodsIn this study, we discovered that changes in Tau availability are linked to global alterations in gene expression that affect multiple neuronal pathways. Comparison with the human temporal region showed that the Tau-dependent modulation of gene expression closely resembles the intermediate stages of Alzheimer’s disease (AD) that precede the definitive pathological condition.ResultsFurthermore, we identified the chromatin remodeling pathway as being significantly affected by Tau in both our cellular model and AD brains, with reductions in heterochromatin markers. Our findings indicate that Tau is able to globally affect the neuronal transcriptome and that its subcellular unbalance changes gene expression in the intermediate stages of AD development. In addition, we found that the chromatin architecture is affected by Tau during the progression of AD.DiscussionThese results provide new insights into the molecular mechanisms underlying early stages of AD development and highlight the central role of Tau and the contribution of nuclear Tau in this process.